The Urgency of Trademark Registration for Business Actors (Case Study of Supreme Court Decision No 575 K / Pdt.Sus-HKI / 2020 Between Ruben Samuel Onsu vs PT Ayam Geprek Benny Sujono) - Nurhani Fithriah (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
Brand registration is very important for business people. A brand is one of the distinguishing entities between the business activities of business actors. The problem occurs when business actors already have a trademark which is then well known in the community but in fact they have not registered the trademark, as experienced by Ruben Samuel Onsu with his Geprek chicken business. However, in its development, it turns out that there are other business actors using the same mark but have registered the mark. This research was conducted using a normative method through a statutory approach and concepts. This research examines the Supreme Court's decision rejecting the appeal from Ruben Samuel Onsu and analyzes the urgency and procedures for trademark registration. Based on the research results, trademark law in Indonesia is regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The terms and procedures for application for registration of a mark are regulated in Article 4 - Article 8 and further regulated in the Regulation of the Minister of Law and Human Rights No. registration of a mark and being recognized as the legal owner of the mark and rights to the mark are obtainedafter the mark is registered. Ruben Onsu's Bensu mark was declared invalid because Ruben Onsu was not the first party to register the mark, and the Supreme Court decided to cancel all trademark applications made by Ruben Onsu.